Prevalence of Insomnia and its Characteristics among Pilgrims in the 2024 Hajj: A Roadmap to Enhancing Health Services (Asian Journal of Pharmaceutics (AJP), 2025)
Religious pilgrimages, such as the Hajj, are widely publicized gatherings that attractmillions of people worldwide. These events can strain the public health resources of the host nation, necessitatinga high level of readiness and response capacity. This study aims to evaluate the Prevalence of Insomnia and itscharacteristics among pilgrims during the 2024 Hajj. Materials and Methods: A cross-sectional questionnairestudy was conducted over one month in 2024 at the Jeddah International Airport. The questionnaire containedsociodemographic, insomnia, and characteristics, comprising 4 binary-scale items; and (3) awareness of emergencycontact numbers for health services and presence of companions in the holy city (2 items). Results: Among the4,721 pilgrims who responded, 614 (13%) reported insomnia symptoms and met the inclusion criteria for finalanalysis. The demographic breakdown of these pilgrims showed that 48.2% (n = 296) were male, with 29%(n = 178) aged 31–40 years and 22.8% (n = 140) aged 41–50 years. The most common insomnia symptoms reportedwere: trouble falling asleep (46.3%), frequent nighttime awakenings (24.4%), difficulty staying awake (10.4%),and feeling unrefreshed after waking up (10.1%). Notably, pilgrims with higher education levels (graduate-levelor literate) reported more sleep-related issues, including difficulty staying awake, unrefreshing sleep, frequentawakenings, and snoring. Conclusion: This study reveals that insomnia symptoms exist among pilgrims, withthe most frequently reported issues being difficulty initiating sleep, waking up multiple times during the night,struggling to stay awake during the day, and waking up feeling unrested. We recommend educating individualson the importance of sleep and promoting awareness of sleep health during pre-hajj preparations. In addition, wesuggest offering counseling services and support groups for pilgrims who may be experiencing sleep disturbances.These services would focus on stress reduction, relaxation techniques, and coping strategies.